2016
DOI: 10.3329/bmj.v44i3.27337
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and digital subtraction angiographic (DSA) evaluation of patients of subarachnoid haemorrhage (SAH) in a tertiary level hospital

Abstract: The present study was undertaken to evaluate the morphological anatomy of cerebral vessels in patients of aneurysmal subarachnoid hemorrhage. The cross-sectional observational study was carried out in the Department of Neurology, Dhaka Medical College Hospital, Dhaka from January 2013 to June 2013. Adult patients of spontaneous subarachnoid haemorrhage (SAH), diagnosed clinically and confirmed by CT scan of the head were included in the study. However, patients who are not capable financially of undergoing Dig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 23 publications
(22 reference statements)
2
6
2
Order By: Relevance
“…In line with the findings of Hassan et al 11 Islam et al 12 and Linn et al 13 sudden headache and vomiting were the most frequent presenting symptom in this study. But vomiting is not a distinctive feature as almost half the patients with non-hemorrhagic thunderclap headache also report vomiting at onset.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In line with the findings of Hassan et al 11 Islam et al 12 and Linn et al 13 sudden headache and vomiting were the most frequent presenting symptom in this study. But vomiting is not a distinctive feature as almost half the patients with non-hemorrhagic thunderclap headache also report vomiting at onset.…”
Section: Discussionsupporting
confidence: 93%
“…Majority of patients were relatively older (45 to 65 years) which corresponds with similar studies conducted by Suarez et al 9 and Suwatcharangkoon et al 10 . Similar to this study, Hassan et al 11 and Islam et al 12 found higher incidence among male (60.0% & 59.8%).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…At present, the three dimensional-digital subtraction angiography (3D-DSA) is the gold standard for diagnosis and evaluation of cerebral aneurysms. But it is an invasive examination with risks [1]. Other timely and safe clinical diagnostic tools still need to improve the prognosis of patients under emergent conditions.…”
Section: Introductionmentioning
confidence: 99%
“…3D-DSA reconstructions allow accurate assessment of aneurysm morphology and accurate demonstration of the anatomic relationship between the aneurysm and the ACoA complex [ 38 ]. However, DSA is a costly and time-consuming invasive examination, with a risk of complications [ 39 ]. Furthermore, in unilateral angiography only the ipsilateral A1 and A2 segments, without association with the bony skull base, are usually clearly demonstrated [ 38 ].…”
Section: Discussionmentioning
confidence: 99%